Urinary p-cresol is elevated in young French children with autism spectrum disorder: a replication study. (September 2014) - Gabriele, Stefano; Sacco, Roberto; Cerullo, Sonia; Neri, Cristina; Urbani, Andrea; Tripi, Gabriele; Malvy, Joëlle; Barthelemy, Catherine; Bonnet-Brihault, Frédérique; Persico, Antonio M.
Abstract The aromatic compound p-cresol (4-methylphenol) has been found elevated in the urines of Italian autistic children up to 8 years of age. The present study aims at replicating these initial findings in an ethnically distinct sample and at extending them by measuring also the three components of urinary p-cresol, namely p-cresylsulfate, p-cresylglucuronate and free p-cresol. Total urinary p-cresol, p-cresylsulfate and p-cresylglucuronate were significantly elevated in 33 French autism spectrum disorder (ASD) cases compared with 33 sex- and age-matched controls (p < 0.05). This increase was limited to ASD children aged ≤8 years (p < 0.01), and not older (p = 0.17). Urinary levels of p-cresol and p-cresylsulfate were associated with stereotypic, compulsive/repetitive behaviors (p < 0.05), although not with overall autism severity. These results confirm the elevation of urinary p-cresol in a sizable set of small autistic children and spur interest into biomarker roles for p-cresol and p-cresylsulfate in autism.